2019
DOI: 10.1007/s13337-018-00507-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and phylogenetic analysis of avipoxvirus isolated from birds around Jammu

Abstract: Domesticated fowls, pigeons and turkey birds were screened for avipoxvirus infection from different areas in Jammu region. Based on typical pox lesions the overall occurrence in fowl was found to be 18.52%, 17.03% in pigeons and 57.14% in turkeys. Mortality recorded in chicks was 41.96%, 45.36% in squabs, 100% in poults, and 20.00% in adult turkeys. Both cutaneous and diphtheritic forms of the disease was observed of which the latter was particularly prevalent in young birds. One sample of putative fowlpox vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…Our study revealed that the morbidity/mortality percentage in APV infections is similar to the previous reports, in which, rates were found to be more than 50% (Ivanov, Kril, & Sainova, ; Skinner, ; Tripathy, ). However, our results differed from the recently studied avipox outbreak, in which the percentages varied from 17% to 18% and 41 to 45%, respectively (Sharma et al, ). The difference in severity may be due to the presence of higher chicks or squabs population (0‐8W) within the study group (Pathak, ; Pathak, Goswami, Sharma, & Mukit, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study revealed that the morbidity/mortality percentage in APV infections is similar to the previous reports, in which, rates were found to be more than 50% (Ivanov, Kril, & Sainova, ; Skinner, ; Tripathy, ). However, our results differed from the recently studied avipox outbreak, in which the percentages varied from 17% to 18% and 41 to 45%, respectively (Sharma et al, ). The difference in severity may be due to the presence of higher chicks or squabs population (0‐8W) within the study group (Pathak, ; Pathak, Goswami, Sharma, & Mukit, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Out of various field samples, one each of FWPV and PGPV were adopted (in triplicate) on CAM through three passage levels. The isolates have been earlier verified by partial amplification of P4b gene and confirmed as FWPV and PGPV by alignment with published sequences (Sharma et al, 2019). The eggs were candled daily and opened on 5 d.p.i.…”
Section: Chorio-allantoic Membrane Inoculation Of Virus In Chicken Embryonated Eggsmentioning
confidence: 93%
“…In our laboratory, domesticated fowls, pigeons and turkey birds were screened for avipoxvirus infection from different areas in Jammu region, India, and on the basis of the phylogenetic analysis of the partial P4b gene sequences, three different isolates were identified as Fowlpox virus (FWPV), Pigeonpox virus (PGPV) and Turkeypox virus (TKPV) respectively (Sharma et al, 2019); and it was also found that the FWPV and TKPV were phylogenetically 99% related within clade 1, while PGPV was found to belong to clade 2. Since differences in CPE on CAM by different Avipoxviruses (APV) have been earlier reported (Manarolla et al, 2010;Abdallah and Hassanin, 2013;Offerman et al, 2013) it was proposed to attempt isolation of the viruses on CEE.…”
Section: Introductionmentioning
confidence: 99%
“…Once introduced to a new geographic area, APV can quickly spread among individuals lacking proper husbandry practices and elevated stocking densities that lead to close contact with infected and susceptible individuals. As continuously, the outbreak of APV is being reported from India in different birds from diverse geographical regions for decades (Pawar et al 2011;Sahu et al 2020;Sharma et al 2019).…”
Section: Discussionmentioning
confidence: 99%